Financial statement analysis (McGraw-Hill, 1994)
The book is organized into five parts. The first part covers the relation between financial statement information and the stock market, which is where financial statement information is most widely and actively used. The second part introduces cash flows and accounting accruals, it then includes four articles on alternative methods of accounting and their effects on analyzing financial statements. The third part covers earnings forecasting, including: statistical time series models that use only past earnings to forecast future earnings; models that use information in financial statements, other than earnings, to forecast earnings; properties of professional financial analysts' earnings forecasts; and the performance of the Value Line Investment Survey. The fourth part introduces the analysis of risk, from the perspectives of both lenders and stockholders. Each part begins with an introduction that places tha part in perspective and briefly describes the articles contained in it. In each part's introduction, references to articles reproduced in this book are set in bold. Other references are to sources that are listed at the end of the book